2012
DOI: 10.1016/j.jaac.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Inhibition and Risk for Developing Social Anxiety Disorder: A Meta-Analytic Study

Abstract: Objective Behavioral inhibition (BI) has been associated with increased risk for developing social anxiety disorder (SAD); however, the degree of risk associated with BI has yet to be systematically examined and quantified. The goal of the present study was to quantify the association between childhood BI and risk for developing SAD. Method A comprehensive literature search was conducted to identify studies that assessed both BI and SAD. Meta-analyses were performed to estimate the odds ratio (OR) of the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
412
3
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(461 citation statements)
references
References 55 publications
16
412
3
8
Order By: Relevance
“…AT is a trait-like phenotype that is evident early in life, stable over time, associated with increased amygdala reactivity to novelty and potential threat, and expressed similarly in children and young nonhuman primates (1)(2)(3)(4)(5)(6). Extreme dispositional anxiety and behavioral inhibition in childhood is a wellestablished risk factor for the internalizing spectrum of psychiatric disorders, including anxiety and major depression (5,7,8). These disorders are highly prevalent and associated with substantial morbidity and mortality (9,10).…”
mentioning
confidence: 99%
“…AT is a trait-like phenotype that is evident early in life, stable over time, associated with increased amygdala reactivity to novelty and potential threat, and expressed similarly in children and young nonhuman primates (1)(2)(3)(4)(5)(6). Extreme dispositional anxiety and behavioral inhibition in childhood is a wellestablished risk factor for the internalizing spectrum of psychiatric disorders, including anxiety and major depression (5,7,8). These disorders are highly prevalent and associated with substantial morbidity and mortality (9,10).…”
mentioning
confidence: 99%
“…This temperament places the child at risk for SoAD. 103,104 A recent meta-analysis showed that behavioral inhibition was associated with a seven-fold increased risk for developing SoAD. Given that 15% of infants are classified as behaviorally inhibited and about half of them will develop social anxiety this is one of the most consistent risk factors for social anxiety.…”
Section: Behavioral Inhibition and Anxiety Sensitivitymentioning
confidence: 99%
“…Given that 15% of infants are classified as behaviorally inhibited and about half of them will develop social anxiety this is one of the most consistent risk factors for social anxiety. 103 Anxiety sensitivity is another dimensionally distributed trait that, like behavioral inhibition, has been linked to pediatric anxiety. Anxiety sensitivity involves beliefs that anxious symptoms will have harmful physical, psychological, or social consequences to the individual.…”
Section: Behavioral Inhibition and Anxiety Sensitivitymentioning
confidence: 99%
“…In a social environment, children with weak inhibition abilities tend to withdraw from social environment (Rubin, Coplan, & Bowker, 2009;Walker, Henderson, Degnan, Penela, & Fox, 2015), has a significant risk of developing social anxiety disorder, and not being assertive (Clauss & Blackford, 2012). In academic terms, children with moderate inhibition abilities tend to find it difficult to focus on learning at home or school.…”
Section: Introductionmentioning
confidence: 99%